Addressing the challenges of water-energy-food nexus programme in the context of sustainable development and climate change in South Africa. Issue 7 (14th June 2022) - Adom, Richard Kwame; Simatele, Mulala Danny; Reid, Memory
Abstract: The fast-growing pace of the world's population and the increasing pressure exerted on global life supporting natural systems due to amplified natural resource use and consumption coupled with the impacts of climate change necessitates the development of innovative technologies and comprehensive policy frameworks to address the looming crisis in the water, energy and food nexus. As the 30th driest country globally, South Africa has embarked on and enacted a pro-water-energy and food nexus policy which aims to create an understanding of the interdependencies of the three components and their influence on socio-economic growth and national development in the face of climate change-induced environmental changes. While these policies and programmes appear to have a sound theoretical basis, their implementation has been hindered by a number of structural and systemic challenges. Using methods inspired by the tradition of participatory research, this paper discusses the strengths and weaknesses of the water-energy-food policy framework in South Africa within the context of its implementation in order to achieve water, energy and food security. The findings of this paper revealed that while some level of progress has been attained to improve the livelihoods of the population using the nexus ecosystem, the broader goal of the concept has failed to materialise due to poor execution of the programme, which is exacerbated by lack of synergies, and establishment of collaborations and partnerships among the relevant actors mandated with the management of the three components and inadequate investment. This paper recommends a broader and coordinated approach to implementing the water-energy-food nexus programme with a broader objective of sustainable development goals (SDGs) framework. HIGHLIGHTS: Analysed policies and implementation challenges of water-energy-food nexus programmes. Lack of awareness, understanding and applicability of the nexus ecosystem. Systemic and structural challenges to the nexus trade offs. Alternative strategies to enhance the programmes. The role of stakeholders to improve the nexus concept.